Environmental effects of natural dyes and syntetic dyes: a comparison - Mahmood, Salwa; Marsi, Noraini; Jalil, Anis Jazira; Mathava, Kumudha (Penerbit UTHM, 2020)
Dyes is important to add colorant on fabrics. The dyeing process makes a fabric colourful and attractive. However, the waste disposed by dyeing process was hazard to environment especially synthetic dyes. Most of the textile industry uses synthetic dyes compared to natural dyes. This happens because natural dyes are difficult to extract its colour. Four types of natural and synthetic dyes were reviewed in this study. It was understood that all types of dyes have its advantages and disadvantages. Natural dyes have poor colour fastness compared to synthetic dyes. Besides, natural dyes can combine with synthetic dyes for greater commercial dyeing. Dyeing is one of the method to beautify the appearance of fabrics. It is a process to add colour to textile products like yarn, fiber and fabrics. Dyeing can be divided into synthetic dyes and natural dyes whereas can be produced either chemically or by plants. Synthetic dyes are man-made and normally made from synthetic resources such as petroleum by-products and earth minerals while natural dyes are from plant and animal sources. Most of the textile industry is using synthetic dyes compared to natural dyes. Natural dyes are hardly to extract their colour and environmentally friendly. Synthetic dyes can be extracted easily but brings harmful effect to environment. Unfortunately, the exact amount of dyes produced in the world is still unknown. It is estimated that the production of dyes to be over 10,000 tons per year. Exact data on the quantity of dyes discharged in the environment are also not available (Forgacs and Cserhátia, 2004).